The Existence Of PT Jamsostek In Social Security Services For Participant Time Working Agreements (PKWT) ( Study at PT Jamsostek (Persero) Belawan Branch) - Jones Parapat (Journal of Law Science, 2020)
One of the rights inherent in human nature and existence is the right to social security. Therefore it is often argued that social security is a universal/general program that must be implemented by all countries. In the 1948 United Nations Universal Declaration of Human Rights Article 22 and Article 25 it is stated that: "Everyone, as a member of society has the right to social security: in the event of unemployment, illness, disability, inability to work, widowhood, old age" . Social security includes labor social security programs which are generally intended to provide protection and welfare for workers. There is no exception for workers based on a Specific Time Work Agreement which basically has different characteristics both in the implementation of their work and in terms of wages which emphasizes more on the Work Agreement agreed between the worker/laborer and the entrepreneur and the term of the working relationship is not permanent as is the case with to permanent workers/labourers. Because of these different characteristics, the regulation also needs to be regulated in a separate regulation, namely the Decree of the Minister of Manpower Number KEP- 150/MEN/1999 concerning the Implementation of the Social Security Program for Workers for Casual Daily Workers, Wholesale and Specific Time Work Agreements.The implementation of the social security program for workers based on a Specific Time Work Agreement (PKWT) in its implementation often does not work as expected which is able to provide protection and welfare / peace of mind for PKWT workers so that the authors are interested in raising this issue as a problem in the thesis. entitled "The Existence of PT Jamsostek (Persero) in Social Security Services for Workers with a Specific Time Work Agreement (PKWT)". This research is expected to be able to answer how the implementation of the labor social security program for PKWT workers, and find out what efforts can be made to ensure the protection of the Labor Social Security for PKWT workers,This research was conducted using library research and field research methods to obtain material as a reference in writing related to the problems of writing this thesis which in the end was able to provide benefits for various related parties in order to provide protection and welfare for workers. work especially for workers based on a Specific Time Work Agreement which in the end can play an active role in increasing economic growth for the welfare of the community and the future development of the nation.